Pengaruh Penggunaan Internet dan Minat Belajar terhadap Prestasi Belajar Mahasiswa Pendidikan Matematika Universitas Nusa Cendana Kupang - Ponsiana Mega Uman; Christine K. Ekowati; Magdalena Wangge (Universitas Nusa Cendana, 2022)
The purpose of this study was to determine the effect of internet use and interest in learning on student achievement in mathematics education at the University of Nusa CendanaKupang simultaneously. The type of research is correlational research and is carried out at the Mathematics Education Study Program of UNDANA Kupang. The population in this study were active students of mathematics education at UNDANA Kupang. The sampling technique used was cluster sampling so that the sample in this study were active students of mathematics education in semester V as many as 82 students. Data collection techniques using online questionnaires and documentation. The data analysis technique used is simple linear regression analysis and multiple linear regression. Hypothesis test using t test and significant level. The results obtained that tvalue > ttable = 2.787 > 1.99006 so that there is a significant influence between internet use on student achievement. The result of the test is that tvalue > ttable = 6.537 > 1.99006 so that there is a significant effect of interest in learning on student achievement. From the multiple linear regression analysis test, Fvalue is 21.251 while the Ftable value is 3.110766 with sig. 0.000. < 0.05 so there is a significant effect between internet use and interest in learning on student achievement.